East-West migration and gender: is there a double disadvantage vis-à-vis stayers? - Anzelika Zaiceva (Institute for the Study of Labor (IZA), 2007)
This paper documents whether female East-West migrants in Germany after the reunification experience a gain or a disadvantage after they moved compared to both stayers and males. It employs panel data techniques to take account of unobserved heterogeneity. I find that migrant women after migration neither experience a drop in relative employment, nor lower relative hourly wages. They do, however, work less hours and have a lower annual income. The results also suggest that for them, the income effect dominates the substitution effect and they substitute market work with home production, specifically with childcare.
urn:nbn:de:101:1-20080401208
Keywords: 330; Binnenwanderung; Regionale Arbeitsmobilität; Geschlecht; Frauenerwerbstätigkeit; Neue Bundesländer; Alte Bundesländer; Deutschland